PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Husnul Faisyah; Muthia Harnida; Mardah, Siti (Jurnal Ilmiah Ekonomi Bisnis, 2024)
Abstract: This research was conducted to determine the effect of liquidity, solvency and profitability on company value. This type of research is associative quantitative research. The population was taken from companies listed on the Indonesia Stock Exchange for the 2017-2021 period and totaled 8 companies. Data was obtained from secondary data taken from the official BEI website. The test tool used was SPSS 29 IBM Version. To obtain the desired results, descriptive tests, normality tests, classical assumption tests, hypothesis tests and multiple linear regression tests were carried out. From the results of the tests carried out, the results were obtained. that the variable X1 (liquidity) effect and is not significant on company value. Solvency Variables have a positive and significant effect on the Y (company value) and profitability have a positive and significant effect on the company's value (Y). Keywords: Liquidity, Solvency, Profitability, Company Value